Oral Health Status of 12-15 Years Old School Going Children in Lucknow City - Rashmi Lata; Shitanshu Malhotra; Madhusudan Krishna; Manu Narayan; Om Veer Singh; Neeraj Kumar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: To evaluate oral health status of 12-15 years old school going children in Lucknow.Material and Method: The study was carried out during January 2019 to August 2019. Total 1200 schoolgoing children of age 12 to 15 years were taken in this study. Schools were selected by multistage randomsampling technique. There were total 814 schools in the Lucknow, out of which 24 schools were taken inthe study area in which 11 were government schools and remaining 13 were private schools. Closed-endedquestionnaire consisting of demographic data, three questions of oral hygiene practices and four indiceswere used. Dental examination was done to assess the dental caries status, oral hygiene status, presence ofmalocclusion and gingival status. Data was analysed by using SPSS software version 21.Results: Toothpaste and toothpowder were used as material by 73.2% and 25.3% of the subjects respectively.The maximum DMFT scores was seen among 12 years, then 15 years, then 14 years and least in 13 years.Maximum 13 years old students reported fair oral hygiene index. The comparison of study participants withregard to age of the student was not found to be significant.Conclusion: To conclude, the results of the present study confirmed that there is increased prevalence ofmalocclusion among children in the 12 to 15 year age group. Among all the age group, oral hygiene statuswas observed to be fair.